Avaliação da contaminação das águas subterrâneas por atividade cemiterial na cidade de Maceió - Silva, Florilda Vieira da (2012)
The potential for contamination of groundwater by cemetery activities in the city of Maceió, in this work, is evaluated through analysis of its physico-chemical and bacteriological quality. The cemeteries selected for this evaluation are located in medium vulnerability areas, in where groundwater level is near to the ground surface. Two cemiteries were chosen for the the research, Nossa Senhora Mãe do Povo and São José, located in the neighborhoods of Jaraguá and Trapiche, respectively. Besides the wells located within the cemiteries area another well, located upstream of Nossa Senhora Mãe do Povo Cemetery (background) was monitored. The physical, chemical and microbiological characteristics of groundwater have been modified by the use and occupation of land, by the local climate, the soil type and lack of sanitation. The microbiological analysis indicated pollution of fecal origin. The hygienic and sanitary conditions of the studied waters are not satisfactory, because the samples showed E. coli and / or total coliform. Clostridium perfringens were also detected (indicative of remote contamination), proteolytic bacteria and heterotrophic bacteria, suggesting contamination by the presence of organic matter in aquifers groundwater. It was observed the presence of proteolytic bacteria in the São Jose Cemetery groundwater, suggesting necrochorume contamination. As for to physical and chemical parameters, some of them showed off the reference standards (color, turbidity, nitrate and dissolved total solids) for drinking water according to Decree 2914/211 of the Ministry of Health